HoloFoodR: a statistical programming framework for holo-omics data integration workflows - Borman, Tuomas; Sannikov, Artur; Finn, Robert D; Limborg, Morten Tønsberg; Rogers, Alexander B; Kale, Varsha; Hanhineva, Kati; Lahti, Leo (Oxford University Press (OUP), 2026)
Summary: Holo-omics is an emerging research area that integrates multi-omic datasets from the host organism and its microbiome to study their interactions. Recently, curated and openly accessible holo-omic databases have been developed. The HoloFood database, for instance, provides nearly 10,000 holo-omic profiles for salmon and chicken under controlled treatments. However, bridging the gap between holo-omic data resources and algorithmic frameworks remains a challenge. Combining the latest advances in statistical programming with curated holo-omic data sets can facilitate the design of open and reproducible research workflows in the emerging field of holo-omics.
Availability and implementation: HoloFoodR R/Bioconductor package and the source code are available under the open-source Artistic License 2.0 at the package homepage https://doi.org/10.18129/B9.bioc.HoloFoodR.
Supplementary information: Available in the package vignette https://ebi-metagenomics.github.io/HoloFoodR/articles/case_study.html.
Keywords: bioconductor; data integration; holo-omics; metabolomics; metagenomics; multi-omics.